Association of Iron Deficiency Anemia and Breastfeeding in Children - Javed, Sumaiya; Ghafoor, Tariq; Khan, Qamar-Uz-Zaman; Ikram, Farooq; Tahir, Muhammad; Naz, Shagufta (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency and association of iron deficiency anemia in breastfed children less than equal to six months of age. Study Design: Prospective observational study Place And Duration of Study: Pak Emirate Military Hospital & CMH, Rawalpindi Pakistan from Sep 2020 to Mar 2021 Methodology: All children less than equal to 6 months of age of either sex having birth parameters of term gestation (between 37 and 42 weeks), birth weight 2500 grams or more, uneventful postnatal course were consecutively enrolled. Iron deficiency anemia was defined based on serum ferritin concentration <30 micrograms/L and hemoglobin concentration <11 g/dl. History of breastfeeding status along with the other predictor variables were noted. Results: Of 315 children 73(23.2%) were exclusively breast fed and 242(76.8%) were non-exclusively breastfed. A significantly higher frequency of iron deficiency anemia was observed in exclusively breast fed as compared to non-exclusively breastfed children, i.e., 26(35.6%) and 36(14.9%) respectively. Moreover, age (p-value <0.001), gender (p-value <0.001), residence (p-value <0.001), mother’s educational status (p-value <0.001), socioeconomic status (p-value <0.001), number of children in family (p-value <0.001), mode of delivery (p-value <0.001), and smokers in the family (p-value 0.037) was found to be significantly associated with iron deficiency anemia. Conclusion: Iron deficiency anemia was found significantly higher in our cohort with considerably higher prevalence in exclusive breastfed children.